State and county level legislative approaches to address racial/ethnic health inequities in Maryland (2012–2021) - Makeda Walelo; Kellee White Whilby (Frontiers in Public Health)
IntroductionPublic policies and legislative approaches are used to address racial health inequities. While most recent studies examine federal and state-level legislative activity, a paucity of analyses characterize policies enacted in a single state and across local jurisdictions. To address this gap, we identify racial health equity policies in the state of Maryland and describe key features and themes.MethodsA legal mapping study and content analysis was conducted. Maryland policies and legislative activity adopted at the state or county level (2012–2021) were identified by systematically searching Westlaw and state and county government legislative databases. Information for each policy was ascertained and analyzed to identify content domains.ResultsWe identified 22 state-level policies and 10 county-level policies and actions that explicitly addressed racial health inequities. Six domains were identified: healthcare and public health cultural competence; disease-specific care and outcomes; access to healthcare services; social determinants of health; collection action and research infrastructure; and structural racism. At the state- and county- level, most policies pertained to the healthcare and public health cultural competence domain. Of Maryland’s 24 counties, only 8 (33%) passed health equity policies and implemented equity-specific policy priorities.ConclusionThis study provides a snapshot of the Maryland policy landscape and suggests an increasing prioritization of equity policy at the state and county levels. While policies address issues ranging from cultural competence to structural racism, policy content differed by level of jurisdiction. Future efforts to critically evaluate the impact of specific policies on health inequities are needed.